OXIDATIVE STRESS AND METABOLIC RESPONSES OF ACUTE WATERBORNE COPPER EXPOSURE IN KILLIFISH, FUNDULUS HETEROCLITUS - RANSBERRY, K. E. (My University, 2013)
Copper (Cu) is an essential trace metal, but many aspects of its toxicity remain unclear, particularly in seawater (SW) and little is known regarding the interaction effects of Cu and hypoxia. Few studies have examined the effects of excessive waterborne metals, like Cu, on fish species under saline environment conditions and in combination with other natural stressors, like hypoxia. I first examined the acute effects of sublethal waterborne Cu and hypoxia on the oxidative stress response in freshwater (FW)-acclimated adult killifish (Fundulus heteroclitus), a model euryhaline teleost, which highlighted the need to investigate metabolic responses including oxygen consumption rates (MO2). I found that hypoxia had no effect on Cu accumulation and that Cu induced antioxidant protection pathways and reduced oxidative capacity in a tissue-specific manner. I found that hypoxia may have an antagonistic effect on Cu-induced lipid peroxidation, although this pattern was not observed in all tissues.
I then examined the acute effects of sublethal waterborne Cu on oxidative stress and metabolic responses in FW- and SW-acclimated adult killifish. I found that the oxidative stress and metabolic responses induced by Cu in killifish acclimated to SW differed only slightly from those in FW. I found that Cu had no effect on oxygen consumption rates after 96-h exposure in both FW and SW-acclimated fish, however Cu greatly reduced opercular frequency. In addition, we found that Cu-induced antioxidant protection pathways, although the response differed depending on the specific enzyme. This thesis has advanced our understanding of Cu toxicology in terms of oxidative stress and metabolic responses in freshwater and marine environments and emphasized the importance of utilizing multiple physiological endpoints. Hopefully, this work will contribute to the future development of Cu water quality criteria and building more accurate predictive and regulatory models.
Keywords: Copper; Toxicity; Hypoxia; Oxidative stress; Metabolic responses; Salinity; Biology; Other Physiology; Biology